2020
DOI: 10.1002/jcp.29971
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen enhances browning in adipose tissue by M2 macrophage polarization via heme oxygenase‐1

Abstract: Loss of ovarian function results in increased fat mass, leading to the accumulation of adipose tissue macrophages that participate in chronic inflammation. We hypothesized that ovariectomy (OVX)-induced increases in body weight and fat mass are associated with decreased adipose tissue (AT) browning due to estrogen (E 2) deficiency. In mice, OVX decreased AT browning along with increased body weight, fat mass, and size of lipid droplets 12 weeks after surgery. Exogenous E 2 recovered the OVX-induced changes. AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…5), this nding is in line with our previous literature [7]. Sul et al further indicated exogenous administration of E 2 enhanced browning in vivo and invitro, which might result from the anti-oxidant activity of E 2 [26]. ALA supplementation increased the serum levels of irisin, suggesting the browning effects of ALA is partly mediated via irisin production.…”
Section: Discussionsupporting
confidence: 90%
“…5), this nding is in line with our previous literature [7]. Sul et al further indicated exogenous administration of E 2 enhanced browning in vivo and invitro, which might result from the anti-oxidant activity of E 2 [26]. ALA supplementation increased the serum levels of irisin, suggesting the browning effects of ALA is partly mediated via irisin production.…”
Section: Discussionsupporting
confidence: 90%
“…For example, loss of estrogens by ovariectomizing reduced WAT expression of glutathione peroxidase 3 ( Gpx3) ( 41 ), a gene important for the protection of cells from oxidative stress in the form of reactive oxygen species (ROS) ( 78 ). Furthermore, E2 reduced ROS levels and enhanced browning in female mouse SAT through promoting macrophage heme oxygenase-1 ( Hmox1 , also known as HO-1 ) expression ( 79 ). Similarly, E2 treatment of 3T3-L1 adipocytes increased expression of genes encoding the ROS reducing antioxidants HO-1, NAD(P)H:quinone oxidoreductase 1 ( NQO1 ) and glutamate-cysteine ligase ( GCL ), directly in the adipocytes ( 80 ).…”
Section: Mechanisms Of Action and Metabolic Regulation By Estrogen In...mentioning
confidence: 99%
“…The cardiac HO-1 expression and activity are reduced in response to ovariectomy [ 57 ]. E 2 increases HO-1 expression in aorta [ 58 ], prostatic stoma [ 59 ], endothelial progenitor cells [ 60 ], and macrophages [ 61 ], leading to decreased reactive oxygen species (ROS) levels. In addition, E 2 inhibits the endothelin-induced inhibition of HO-1 expression in cardiomyoblasts [ 62 ].…”
Section: Discussionmentioning
confidence: 99%